2017
DOI: 10.1177/1086026616687014
|View full text |Cite
|
Sign up to set email alerts
|

Visuality as Greenwashing: The Case of BP and Deepwater Horizon

Abstract: We use a visual semiotic approach to explore how BP utilized the power of the visual after the 2010 Deepwater Horizon disaster. Through the careful construction and use of images on its corporate website, BP narrated a visual story that helped the company construct a “logic of representation” when its “logic of practice” became problematic and heavily scrutinized. We argue that the BP case has wider applicability in understanding how companies deploy the visual to create a reality that averts the limelight fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 77 publications
(126 reference statements)
0
34
0
2
Order By: Relevance
“…Indeed, reactive environmental strategies are not equivalent to greenwashing strategies. A proactive or positive green practice, such as green communication, may simply be a method of impression management [77] and may not create value. Some studies have tried to examine whether environmental strategies could have a better market value in the capital market, which may represent greenwashing behavior when environmental strategies fail to create market value [78].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reactive environmental strategies are not equivalent to greenwashing strategies. A proactive or positive green practice, such as green communication, may simply be a method of impression management [77] and may not create value. Some studies have tried to examine whether environmental strategies could have a better market value in the capital market, which may represent greenwashing behavior when environmental strategies fail to create market value [78].…”
Section: Discussionmentioning
confidence: 99%
“…Given the proliferation of environmental concerns and commitments to reduce environmental impacts at both national and international levels (Eccles & Serafeim, ), a growing number of companies started to communicate aggressively their involvement in reducing their environmental footprint, by excessively emphasizing their commitment rather than real efforts. For instance, Kassinis and Panayiotou () have scrutinized the website pages of BP, involved in one of the largest environmental disasters in human history, from 2014 to 2016 and found that the visual power of web images can be used to enhance a visual decoupling between practices and messages. A similar discrepancy between the image projected toward the external environmental and actual internal practices is the core content of Hawthorne (), who focused her attention on high‐profile companies such as Apple, Starbucks and American Apparel.…”
Section: Introductionmentioning
confidence: 99%
“…Volkswagen received negative publicity in 2015 when the US Environmental Protection Agency revealed that the company had deliberately tampered with vehicles during emissions testing but had actively concealed the information from regulators and consumers (for example Rhodes, 2016; Siano, Vollero, Conte, & Amabile, 2017). BP came under pressure when it was found responsible for the largest accidental oil spill in the petroleum industry’s history at Deepwater Horizon, despite its rhetoric claiming strong environmental credentials (Kassinis & Panayiotou, 2018). CEOs also feel they are under increased scrutiny because of the proliferation of social media and the 24/7 news cycle that has emerged (Per-Ola Karlsson, 2017).…”
mentioning
confidence: 99%